PERNIKAHAN DI USIA MUDA KARENA PERMINTAAN ORANG TUA DI KECAMATAN MUARA BANGKAHULU - Hartono, Jaudi (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2017)
The existence of marriage at a young age caused by the request of parents in the district of Muara Bangkahulu into a phenomenon that wanted to be examined by the author.  What is the underlying  cause of underage marriage due to parents’  requests in Muara Bangkahulu Subdistrict  and  how  Islamic law’s view of marriage at a young age caused by parental demand is a matter of concentration. This research is field research using descriptive analytic method. The results of this study indicate that the cause of marriage at a young age caused by the demand of parents in Muara Bangkahulu District is due to economic factors, socio-cultural and parents’ concerns about  the negative  impact  of globalization.  While the view of Islamic law against  marriage at a young age because the request of parents is to allow parents to ask their children  to marry even though still at a young age as long as there  is a clear reason and not harm the child.